FREEZE-DRYING AND ITS IMPORTANCE - ΣΕΪΜΕΝΗΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
The history, the principles and the importance of freeze-drying in biology and chemistry are briefly reported. For several decades this technique. Has been mainly used for drying biological products, antibiotics, microorganisms, pharmaceuticals, complex tissues and food products. Beside these applications further prospectives are opened for the preparation of new chemical products.